Building Human Visual Attention Map for Construction Equipment Teleoperation - Fan, Jiamin; Li, Xiaomeng; Su, Xing (Frontiers in Neuroscience, 2022)
Construction equipment teleoperation is a promising solution when the site environment is hazardous to operators. However, limited situational awareness of the operator exists as one of the major bottlenecks for its implementation. Virtual annotations (VAs) can use symbols to convey information about operating clues, thus improving an operator’s situational awareness without introducing an overwhelming cognitive load. It is of primary importance to understand how an operator’s visual system responds to different VAs from a human-centered perspective. This study investigates the effect of VA on teleoperation performance in excavating tasks. A visual attention map is generated to describe how an operator’s attention is allocated when VAs are presented during operation. The result of this study can improve the understanding of how human vision works in virtual or augmented reality. It also informs the strategies on the practical implication of designing a user-friendly teleoperation system.